IC 9332 Preventing Coal Mine Groundfall Accidents: How To Identify And Respond To Geologic Hazards And Prevent Unsafe Worker Behavior - Staff (The National Institute for Occupational Safety and Health (NIOSH), 1992)
A major emphasis of the U.S. Bureau of Mines is to perform research on the prevention of fatal accidents at mining operations. The leading cause of fatalities in the underground coal mining industry is groundfalls. This proceedings volume presents several new developments that are helping to prevent fatalities and reduce injuries by groundfalls. The papers focus on the problem from two different perspectives. About half of the papers present information and techniques that can be used to train and motivate miners to protect themselves from groundfalls. The other papers explain how to identify and respond to various geologic conditions that affect the stability of the mine roof. Of the 95 groundfall fatalities that occurred during 1986-90, 75% took place in Kentucky, West Virginia, and Virginia. The rate of groundfall fatalities was much higher at small mines. During 1986-90, the rate of groundfall fatalities at mines employing fewer than 20 people was 4.3 times higher than the rate for larger mines. Because so many groundfall fatalities are occurring at relatively small mines in the southern Appalachian coalfields, many of the papers focus specifically on the needs of this category of mine operations.